2019
DOI: 10.1002/cam4.2594
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐blockers exert potent anti‐tumor effects in cutaneous and uveal melanoma

Abstract: Background Melanoma is a life‐threatening group of cancers mainly affecting the skin (cutaneous melanoma, CM) and the eyes (uveal melanoma, UM). Nearly half of patients with UM develop liver metastases regardless of the primary treatment. For this reason, adjuvant therapy to prevent disease progression is essential to improve survival of patients with melanoma. Beta‐adrenoceptors (β‐AR) have emerged as novel targets to inhibit tumor growth and dissemination in CM, but have not been investigated in UM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
(78 reference statements)
0
27
1
Order By: Relevance
“…Beta-adrenoceptors (B 1–2 -AR) have emerged as novel targets to inhibit tumor growth and dissemination in cutaneous and uveal MM [ 354 , 355 , 356 ]. Beta-blocker use correlates with better overall survival in metastatic MM, protects patients from disease recurrence and improves the efficacy of immunotherapies in mice [ 354 , 355 , 356 ].…”
Section: Therapeutic Suppression Of Mir-21mentioning
confidence: 99%
See 1 more Smart Citation
“…Beta-adrenoceptors (B 1–2 -AR) have emerged as novel targets to inhibit tumor growth and dissemination in cutaneous and uveal MM [ 354 , 355 , 356 ]. Beta-blocker use correlates with better overall survival in metastatic MM, protects patients from disease recurrence and improves the efficacy of immunotherapies in mice [ 354 , 355 , 356 ].…”
Section: Therapeutic Suppression Of Mir-21mentioning
confidence: 99%
“…Beta-adrenoceptors (B 1–2 -AR) have emerged as novel targets to inhibit tumor growth and dissemination in cutaneous and uveal MM [ 354 , 355 , 356 ]. Beta-blocker use correlates with better overall survival in metastatic MM, protects patients from disease recurrence and improves the efficacy of immunotherapies in mice [ 354 , 355 , 356 ]. Catecholamine stimulation of B 1-2 -AR via activation of STAT3 upregulates miR-21 expression [ 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 ], whereas beta-blocker treatment attenuates miR-21 expression [ 364 ].…”
Section: Therapeutic Suppression Of Mir-21mentioning
confidence: 99%
“…Moreover, there is recent evidence of potent antitumor effects in UM cells following nonselective beta-blocker administration, and concurrent expression of β1 and β2 adrenoceptors in UM specimens. These findings suggest that further investigation is needed in the context of clinical trials for adjuvant scope [ 112 ]. Current clinical trials in the adjuvant setting are summarized in Table 2 .…”
Section: Adjuvant Therapies and Surveillance Of Ummentioning
confidence: 99%
“…These studies also confirmed the role of β-ARs in the modulation of angiogenesis and demonstrated that non-selective β-AR antagonists, but not β1-AR selective antagonists, promote apoptosis of cancer cells [ 40 , 41 , 42 ]. Propranolol exerts potent anti-tumoral effects, attenuating migration, reducing vascular endothelial growth factor (VEGF) secretion and inducing apoptosis in both cutaneous and uveal melanoma in a dose-dependent manner [ 43 ]. Anti-angiogenic effect of propranolol has also been well described in infantile hemangiomas (IHs) and retinopathy of prematurity [ 39 ].…”
Section: β-Ars In Melanomamentioning
confidence: 99%